INDONESIAN FLIGHT ATTENDANTS’ PERCEPTIONS OF DIALECT VARIETIES - Andayani, Widya; Damanik, Sisila Fitriani; Hutasuhut, Mahmud Layan; Anshari, Rudi (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2023)
This research was aimed to examine flight attendants’ perceptions of dialect varieties in Indonesia. The researchers concerned in flight attendants' perceptions of various dialects used by partners, as well as passengers' attitudes toward the flight attendants' dialect. This research was conducted by using qualitative method. The participantswere 2 flight attendants which have different background cultures yet work in one aviation. In this research, direct quotations were presented unaltered. Each direct quotation is followed by a descriptive abbreviation noting the source of the quotation. The participants answered some questions that was given. Interviews were conducted using Whatsapp application because it was impossible to do face-to-face interviews with the participants in COVID-19 pandemic. Each interview took 30 to 40 minutes. Interviews were taped with a voice note feature on Whatsapp. The results revealed that each flight attendant saw the dialect variations in partners as an interesting thing to respect as long as the partner communicated well and politely, the passenger understood and got the point. In terms of the passengers' reactions to the flight attendants' dialect, there were possitive and negative from the passengers.